SAT0273 Lower socioeconomic status and smoking are associated with greater radiographic disease severity in axial spondyloarthritis. (23rd January 2014) - Gensler, L.S.; Yoon, G.; Learch, T.J.; Ward, M.M.
Abstract : Background: Radiographic severity and progression are important outcome measures in Ankylosing Spondylitis (AS). In the past, the Bath Ankylosing Radiology Index (BASRI) was the primary measure used. More recently, the modified Stoke Ankylosing Spondylitis Spine Score (mSASSS) has been studied. However, most recent studies have reported on radiographic disease progression, not severity. Prior studies that have used the BASRI for radiographic severity have looked at patients with long-standing disease. Objectives: To determine the clinical and demographic characteristics associated with radiographic spinal disease severity, as defined by the mSASSS in a heterogeneous single-center cohort of patients with axial Spondyloarthritis (SpA). Methods: This is a cross-sectional analysis from the baseline visits for patients consecutively enrolled at one center. Patients were enrolled if they met Assessment of SpondyloArthritis (ASAS) criteria. Radiographs were performed at baseline (including Pelvis and spinal films). Clinical and demographic features were assessed by univariate analysis and then by Multivariate linear regression. Results: One-hundred-and-seventy patients were enrolled. of which, 73.5% met Modified New York (NY) criteria for AS and 26.5% met ASAS criteria for axial SpA. Of those not meeting modified NY criteria, all but 2 had radiographic sacroilitis. This was an ethnically diverse group, with Caucasian patients accounting for 60% of the cohort. Baseline characteristics are outlined in the table 1 . Of 170 patients, 138 had complete data available for analysis. In the multivariate analysis, a higher mSASSS was associated with male gender (coefficient = 5.52, p=0.02, 95% CI 0.81; 10.23), disease duration (coefficient = 0.54, p<0.0001, 95% CI 0.31; 0.77), older age at onset (coefficient = 0.31, p=.02, 95% CI .05; .56) a lower socioeconomic status (SES), as defined by years of education (coefficient = -1.12, p=0.002, 95% CI -1.83; -0.41) and smoking (in pack-years) (coefficient = 0.5, p=0.001, 95% CI 0.21; 0.79). There was a trend to significance with non-Caucasian ethnicity (coefficient = -3.96, p=0.08, 95% CI -8.32; 0.4) and having a first-degree relative with AS (coefficient = 5.12, p=0.08, 95% CI -0.55; 10.78). Table 1 . Baseline characteristics and Univariate analysis Conclusions: Lower SES and smoking are independently associated with greater radiographic disease severity in Axial SpA. Further studies are needed to explore the relationship of how SES relates to radiographic damage and how smoking affects bone health in Axial SpA. References: Michael M. Ward, Matthew R. Hendrey, James D. Malley et al., Arthritis Care & Research 2009 Vol. 61(7): pp. 859-66 Disclosure of Interest: None Declared